Beyond Reading Outcomes: Unpacking the Implementation Dynamics of Qur'anic Literacy Programs in Islamic Junior High Schools - Melindatin Maghfiroh; Elok Rufaiqoh; Muhammad Umar Hasibullah (Al-Qalam Institue, 2026)
This study aims to analyze the implementation of the Qur’an Reading and Writing (BTQ) program in improving students’ Qur’anic reading skills. This research employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation involving the school principal, BTQ teachers, and students. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while triangulation was applied to ensure data credibility. The findings reveal that the BTQ program was implemented systematically through demonstration and imitation methods, in which teachers modeled Qur’anic recitation and students repeated it. This approach effectively improved students’ reading fluency, accuracy in applying tajwid rules, and mastery of makhārij al-ḥurūf. Furthermore, the program fostered students’ self-confidence, established regular Qur’an reading habits, and strengthened their religious character. Despite challenges such as differences in students’ initial abilities and limited learning facilities, the program demonstrated significant positive outcomes. These findings imply that the BTQ program should be sustained and further developed as an effective strategy for enhancing Qur’anic literacy and supporting students’ religious character development.